Emergence of Neonatal Sepsis Caused by MCR-9- and NDM-1-Co-Producing Enterobacter hormaechei in China - Chen, Chunlei; Xu, Hao; Liu, Ruishan; Hu, Xinjun; Han, Jianfeng; Wu, Lingjiao; Fu, Hao; Zheng, Beiwen; Xiao, Yonghong (Frontiers in Cellular and Infection Microbiology, 2022)
Mobile colistin resistance (mcr) genes represent an emerging threat to public health. Reports on the prevalence, antimicrobial profiles, and clonality of MCR-9-producing Enterobacter cloacae complex (ECC) isolates on a national scale in China are limited. We screened 3,373 samples from humans, animals, and the environment and identified eleven MCR-9-positive ECC isolates. We further investigated their susceptibility, epidemiology, plasmid profiles, genetic features, and virulence potential. Ten strains were isolated from severe bloodstream infection cases, especially three of them were recovered from neonatal sepsis. Enterobacter hormaechei was the most predominant species among the MCR-9-producing ECC population. Moreover, the co-existence of MCR-9, CTX-M, and SHV-12 encoding genes in MCR-9-positive isolates was globally observed. Notably, mcr-9 was mainly carried by IncHI2 plasmids, and we found a novel 187 kb IncFII plasmid harboring mcr-9, with low similarity with known plasmids. In summary, our study presented genomic insights into genetic characteristics of MCR-9-producing ECC isolates retrieved from human, animal, and environment samples with one health perspective. This study is the first to reveal NDM-1- and MCR-9-co-producing ECC from neonatal sepsis in China. Our data highlights the risk for the hidden spread of the mcr-9 colistin resistance gene.